1993
DOI: 10.1093/bja/71.6.905
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal Intubation in a Mannikin: Comparison of the Belscope With the Macintosh Laryngoscope

Abstract: Tracheal intubation carries a risk of accidental oesophageal intubation; this is increased with inexperienced trainees, and in patients with a difficult airway. The recent introduction of an angulated laryngoscope, the Belscope, may permit a better view of the vocal cords and increase the accuracy of orotracheal intubation. To determine how easy it is to learn to use the Belscope compared with the traditional Macintosh laryngoscope, a group of medical students attempted to intubate a mannikin which had been mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…They also play a core role in teaching skills for basic life support. Their use for teaching intubation and investigating new equipment and techniques is also well established [27,28]. Howells et al [29] described the use of an early manikin for training in tracheal intubation.…”
Section: Didactic Teachingmentioning
confidence: 99%
See 2 more Smart Citations
“…They also play a core role in teaching skills for basic life support. Their use for teaching intubation and investigating new equipment and techniques is also well established [27,28]. Howells et al [29] described the use of an early manikin for training in tracheal intubation.…”
Section: Didactic Teachingmentioning
confidence: 99%
“…They found that despite its limited realism it was a useful training tool for the novice. Others have adjusted the manikins to simulate difficult laryngoscopy [27,28] or have suggested their use in other than the supine position [30], thus increasing their training potential.…”
Section: Didactic Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…This was due to the high tracheal intubation success rates with all devices in our study. One must consider the fact that the success rates for paramedical personnel performing endotracheal intubations using a Macintosh laryngoscope in similar studies are variable [16,17]. The reason for this variability may be attributed to different study settings.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,12 Although the use of a mannequin does not fully replicate intubating conditions in patients, a simulated grade III in an intubation mannequin allows training for and evaluation of intubation techniques in situations that frequently lead to intubation difficulties in humans.…”
Section: Discussionmentioning
confidence: 99%